2017
DOI: 10.1002/jso.24671
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation for unresectable colorectal liver metastases: A systematic review

Abstract: The use of liver transplantation (LT) for liver metastases attempted in the early 1990's was associated with poor perioperative outcomes and unacceptably low overall survival. Recently, there has been renewed interest in LT as a treatment option for colorectal liver metastases (CLM) in countries where organ supply is high. To date, no meticulous analysis about the efficacy, safety and outcomes of LT in CLM patients has been published. We present the first systematic review on the subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 59 publications
0
54
0
3
Order By: Relevance
“…No previous study has published results on the cost‐effectiveness of LTx for patients with CLM. Clinical outcomes have been reported in 11 studies. The only study that included more than ten patients reported 1‐, 3‐ and 5‐year survival rates of 76, 31 and 12 per cent respectively in a series of 25 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No previous study has published results on the cost‐effectiveness of LTx for patients with CLM. Clinical outcomes have been reported in 11 studies. The only study that included more than ten patients reported 1‐, 3‐ and 5‐year survival rates of 76, 31 and 12 per cent respectively in a series of 25 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the early days of liver transplantation (LTx), metastatic colorectal cancer was a contraindication to transplantation owing to the poor results achieved. Before 1995, 1‐ and 5‐year survival rates were 76 and 12 per cent respectively. In recent years, overall survival after LTx has improved, immunosuppressant drugs with antiproliferative properties have been developed, and better diagnostic imaging is available.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of recurrence is a factor in determining whether living donation should be an option. Other comparable situations, such as LDLT for liver metastases from colorectal cancer, raise similar ethical issues in which recurrence rates are high but may provide better survival in select patients than denying transplantation …”
Section: Case 3: Ldlt In a Patient With Hepatocellular Carcinoma Outsmentioning
confidence: 99%
“…Other comparable situations, such as LDLT for liver metastases from colorectal cancer, raise similar ethical issues in which recurrence rates are high but may provide better survival in select patients than denying transplantation. (27) The lack of consensus invariably makes decision making for LDLT in this patient population challenging. The recipient, the transplant team, and the potential donor must all determine their willingness to accept the risks of adverse events to the recipient (eg, graft failure and HCC recurrence) in light of the risk of donor complications.…”
Section: Case 3: Ldlt In a Patient With Hepatocellular Carcinoma Outsmentioning
confidence: 99%
“…Liver transplantation is an alternative option for patients with unresectable metastases (75). Only 0.2-0.3% of all liver transplantations are conducted due to metastatic liver disease from NENs according to the United Network for Organ Sharing database and the European Liver Transplant Registry (76,77).…”
Section: Intra-arterial Liver Treatment (Tace Tae Sirt)mentioning
confidence: 99%